Religious Education in Shaping Professional Religious Character: Analysis of Personality Development Courses in Public Universities - Adilan, Dilan Imam; Mu’min, Mu’min (LPPM Institut Pendidikan Nusantara Global, 2025)
This study explores the role of Islamic Religious Education (IRE) in shaping students' professional religious character within higher education. Amidst growing challenges from globalization, digital culture, and moral relativism, the integration of religious values into university curricula becomes essential. Through a qualitative-descriptive approach supported by survey and document analysis, this research examines how IRE courses contribute to students' moral reasoning, spiritual development, and ethical decision-making. The findings reveal that well-structured religious education enhances students’ understanding of Islamic principles while also fostering leadership, empathy, and resilience. Lecturers employ interactive teaching methods, such as case studies, mentoring, and community engagement, to internalize values of integrity, discipline, and accountability. However, the study also identifies barriers, including religious pluralism, limited instructional time, and the gap between theoretical knowledge and workplace demands. To address these challenges, the study recommends curriculum reform, stakeholder collaboration, and a more interdisciplinary approach linking religion with practical competencies. The research concludes that IRE plays a transformative role not only in shaping students’ moral foundations but also in preparing them to navigate complex professional environments with spiritual integrity and ethical clarity.